The toponym URUa-la-at-ḫa in the letters RSO 23 28-35 and elsewhere - Torrecilla, Eduardo (Antiguo Oriente, 2021)
This brief paper addresses the interpretation of the GN URUa-la-at-ḫa, attested to in seven letters of the RSO 23 volume and allegedly referring to Alalaḫ. Hereby, the toponym is connected to Alatḫa, a settlement previously recorded a handful of times—mainly in the Alalaḫ IV archive—and, without a doubt, to be differentiated from Alalaḫ. The exact location of Alatḫa is unknown, but a general geographical frame for it is proposed.